Does Strike Action Stimulate Trade Union Membership Growth?. (8th June 2016) - Hodder, Andy; Williams, Mark; Kelly, John; McCarthy, Nick
Abstract: Most of the literature on strikes has addressed one of four issues: causation, variation between sectors and countries, trends over time and the relationship between strikes and other forms of collective and individual protest. Very little research has addressed the equally important questions of strike outcomes and trade union membership despite the substantial body of research on the causes of trade union membership decline and strategies for membership growth. In this paper we reverse the usual sequence of trade union membership as a causal factor in the genesis of strikes and examine the impact of strikes on trade union membership levels. After setting out the relevant theory and hypotheses, we use a unique seven‐year dataset of trade union membership joiners and leavers from a major British trade union with a substantial record of strike activity. Controlling for other possible determinants of trade union membership, we find that months in which there is strike action, whether national or local, are associated with a significantly higher rate of membership growth, measured both by the number of joiners and by the ratio of joiners to leavers. Data from new union members suggest that perceived injustice and perceived union effectiveness both motivate the decision to join.